Lake Chad Regional Economic Memorandum : Technical Paper 6. Building Rural Development in the Lake Chad Region - Blankespoor, Brian (World Bank, Washington, DC, 2021)
This paper examines the relationship between access to markets and land cultivation following Berg et al. (2018) using panel methods. Then, author contextualize these results within the broader recent development challenges of the Lake Chad region. The results provide evidence that an increase in market access is associated with an increase in cultivated land and is positively associated with an increase in local agricultural GDP. Even so, conflict from the rise of Boko Haram in the past decade can attenuate gains whereby the proximity to conflict events in the previous year is associated with less cropland across the entire region and less night time lights from over a hundred local markets nearby Lake Chad. This paper makes two contributions. First, the importance of market access as part of economic development is well known, yet advancements in measurement of agricultural activity derived from satellite data and recent data are necessary to gain current insight given developments in the region. Second, this paper contextualizes the findings of market access with local conditions given the numerous conflict events in the past decade from Boko Haram. The rest of this paper is structured as follows. Section two describes the data sources while section three presents the empirical framework, section four presents the results, and section five concludes.